Wednesday

November 26, 2014

November 26, 2014

Posted by **Web10** on Friday, December 2, 2011 at 5:53am.

- Calculus -
**Steve**, Friday, December 2, 2011 at 11:00amf(x) = (-3x+33)^4/3

at x=2, -3x+33 = 27

f(2) = 27^4/3 = 81

f'(x) = -4(-3x+33)^1/3

f'(2) = -4*27^1/3 = -4*3 = -12

f''(x) = 4(-3x+33)^-2/3

f''(2) = 4*27^-2/3 = 4/9

f^{(3)}(x) = 8(-3x+33)^-5/3

f^{(3)}(2) = 8/243

p(x) = f(2) + f'(2)/1! (x-2)^1 + f''(2)/2! (x-2)^2 + f^{(3)}(2)/3! (x-2)^3 + ...

= 81 - 12(x-2) + 2/9 (x-2)^2 + 4/729 (x-2)^3 + ...

**Answer this Question**

**Related Questions**

math (taylor polynomials) - Find the degree 3 Taylor polynomial T3(x) of the ...

calculus-- need help desperately! - The Taylor series about x=5 for a certain ...

calculus - Let f be a function that has derivatives of all orders for all real ...

Calculus - find the 6th degree Taylor polynomial for f(x)=cosx centered at pi/2

Calculus - Find the Taylor Polynomial of order 1 for the function f(x)=arctan(x/...

Calculus - Find the 3rd order for the taylor polynomial in powers of x for the ...

Calculus - Please.... I need your help! I posted this question yesterday and no ...

calculus totally confused - find a first degree polynomial function p(1) whose ...

Algebra 2! - 1.) ƒ(x) = (x^4)/4 − 3x^3 + (23x^2)/2 - 15x. Find the x ...

MATHS - The number 2+3√+5√−−−−−−...